Paul's Use of the Septuagint in Romans 9-11 - Laato, Timo (My University, 2018)
The undertaking of the present study was to examine Paul’s use of the Septuagint in Rom. 9-11, especially the guidelines which affect his interpretation of the Old Testament. To truly come to terms with the issue, a concise overview of the content of his Epistle to the Romans was provided. The opening of the letter (1:2-4), the thematic verses of the letter (1:16-17) as well as the concluding climax of the letter (16:25-26) show that an Old Testament perspective is crucial in all of his theology. In addition, some relevant aspects of Paul’s general way of interpreting the Old Testament were presented and expanded. He repeatedly employs the “promise – fulfillment” scheme in his attempt to define more in-depth the relationship between the Old and New Testament. Further, he frequently draws on typological Bible exposition, rendering the Old Testament accounts and events as a paradigm for the New Testament time span. It follows that the Old Testament as a whole turns out to be a Christological book, referring to the salvation historical development in the New Testament. The Pauline manner of interpreting the Old Testament achieved more precision and accuracy through a comprehensive exegesis of Rom. 9-11 which particularly relate to Israel and their Holy Scriptures. Here all Old Testament quotations (and various Old Testament allusions) were examined one by one. Where appropriate, the original context of the quotations was also observed. As regards quoting the Old Testament, Paul cites recurrently, but not always the Septuagint (or possibly another Greek translation). Sometimes he (or perhaps someone else before him) clearly translates his text directly from the Hebrew. Occasionally, different passages are joined or mixed together under the impression that they as Holy Scripture speak with one voice for the same truth. Everywhere, a strong theological, i.e. Christological, conviction has an important impact on their real meaning. All in all, Paul does not read his Bible arbitrarily. There are crystal clear criteria for assessing his exposition of Scripture. He uses his methods – to put it anachronistically for the sake of clarity – “strictly scientifically.” Yet, his insights and understanding are not built on an atheistic or agnostic foundation, but on the cornerstone, Jesus Christ (cf. Eph. 2:20). Paradoxically, herein lies the stumbling stone: To really understand the Old Testament and therefore also the New Testament, or the other way around, the reader from the outset has to believe in Christ as the fulfillment of Scripture.
Keywords: Paul, Romans, Septuagint, Old Testament, New Testament, promise, fulfillment, typology, Christology, Israel.